The effectiveness of a Teaching program Based on the colored cubes strategy in the Achievement of the basic third-grade students in the mathematics (Journal of Hama University, 2022)
The research aims to know the effect of using Employing the Gube in the collection of basic third-grade students in math, the study was adopted on Quasi- experimental approach, and the research tool formed of Quasi- experimental program designed according to the contradictory events and achievement test, the research sample consisted of (66) male and female students, divided into experimental group consisted of (33) male and female students of (Nahla zedan) School studied by contradictory events, the control group consisted of (33) male and female students of (Yasen Nashar) School studied in the traditional manner, the results indicated the following: - There were statistically significant differences between the mean scores of the students of the experimental group and the control group in the post application to achievement test as a whole, and at every level of knowledge levels in favor of the experimental group.- There were statistically significant differences between the mean scores of students in the experimental group for pre and post of achievement test as a whole, and at every level of knowledge levels in favor of the post application.